Alterations in Olfactory Cortex Volume in Mild Cognitive Impairment and Mild Alzheimer’s Disease Dementia: A Study of Sex-Related Differences - Majed M. Alotaibi; Matteo De Marco; Rona Graham; Annalena Venneri (Brain Sciences, 2025)
Background/Objectives: Aging is one of the greatest risk factors for neurodegenerative diseases such as Alzheimer’s disease (AD). As the disease progresses, neural loss in brain regions, such as the olfactory cortex (OC), i.e., a set of areas including the mediotemporal and orbitofrontal regions, may lead to dysfunction in the sense of smell and affect other brain regions that relate to the olfactory cortex by either afferent or efferent projections. Methods: The objective of this study was to assess sex-related differences in olfactory cortex volume using magnetic resonance imaging in individuals with mild cognitive impairment, probable dementia of the AD type and in healthy older adults, using the Mini-Mental Statement Examination score, years of education, and total intracranial volume as correction factors. Results: Atrophy of the olfactory cortex was observed in patients of both sexes with probable AD dementia. However, at the MCI stage, significant volumetric loss in the OC was detected in females only but not in males. Conclusions: This finding indicates greater pathological effects in this region in females at an earlier disease stage than in males. This study suggests that OC volume loss occurs differently between the sexes in older adults, with volumetric loss being greater in females.